THE HEART OF LIBERTARIANISM: FUNDAMENTALITY AND THE WILL. Issue 1 (2019) - Franklin, Christopher Evan
Abstract: It is often claimed that libertarianism offers an unattractive conception of free will and moral responsibility because it renders free agency inexplicable and irrational. This essay aims, first, to show that the soundness of these objections turns on more basic disagreements concerning the ideals of free agency and, second, to develop and motivate a truly libertarian conception of the ideals of free agency. The central contention of the essay is that the heart of libertarians' ideal of free agency is the ideal of agential fundamentality.